Changes in breathing while listening to read speech: the effect of reader and speech mode - Rochet-Capellan, Amélie; Fuchs, Susanne (Frontiers in Psychology, 2013)
The current paper extends previous work on breathing during speech perception and provides supplementary material regarding the hypothesis that adaptation of breathing during perception “could be a basis for understanding and imitating actions performed by other people” (Paccalin and Jeannerod, 2000, Brain Research, 862(1-2), p. 194). The experiments were designed to test how the differences in reader breathing due to speaker-specific characteristics, or differences induced by changes in loudness level or speech rate influence the listener breathing. Two readers (a male and a female) were pre-recorded while reading short texts with normal and then loud speech (both readers) or slow speech (female only). These recordings were then played back to forty-eight female listeners. The movements of the rib cage and abdomen were analyzed for both the readers and the listeners. Breathing profiles were characterized by the movement expansion due to inhalation and the duration of the breathing cycle. We found that both loudness and speech rate affected each reader’s breathing in different ways. Listener breathing was different when listening to the male or the female reader and to the different speech modes. However, differences in listener breathing were not systematically in the same direction as reader differences. The breathing of listeners was strongly sensitive to the order of presentation of speech mode and displayed some adaptation in the time course of the experiment in some conditions. In contrast to specific alignments of breathing previously observed in face-to-face dialogue, no clear evidence for a listener-reader alignment in breathing was found in this purely auditory speech perception task. The results and methods are relevant to the question of the involvement of physiological adaptations in speech perception and to the basic mechanisms of listener-speaker coupling.